Functional Molecular Materials Insights - Pereira, Laura C. J.; Belo, Dulce (Magnetochemistry, 2024)
In the commemorative Special Issue titled “Insights into Functional Molecular Materials—A Themed Collection Honoring Professor Manuel Almeida on His 70th Birthday”, eminent researchers from around the globe in the field of molecular materials science come together to acknowledge and celebrate the notable scientific contributions of Professor Almeida [...]